Dyads of G‐Quadruplex Ligands Triggering DNA Damage Response and Tumour Cell Growth Inhibition at Subnanomolar Concentration. Issue 47 (1st August 2019) - Doria, Filippo; Salvati, Erica; Pompili, Luca; Pirota, Valentina; D'Angelo, Carmen; Manoli, Francesco; Nadai, Matteo; Richter, Sara N.; Biroccio, Annamaria; Manet, Ilse; Freccero, Mauro
Abstract: Naphthalene diimide (NDI) dyads exhibiting a different substitution pattern and linker length have been synthesised and evaluated as G‐quadruplex (G4) ligands, by investigating their cytotoxicity in selected cell lines. The dyads with the long C7 linker exhibit extremely low IC50 values, below 10 nm, on different cancer cell lines. Contrary, the dyads with the shorter C4 linker were much less effective, with IC values increasing up to 1 μm . Among the three dyads with the longest linker, small differences in the IC50 values emerge, suggesting that the linker length plays a more important role than the substitution pattern. We have further shown that the dyads are able to induce cellular DNA damage response, which is not limited to the telomeric regions and is likely the origin of their cytotoxicity. Both absorption titration and dynamic light scattering of the most cytotoxic dyads in the presence of hTel22 highlight their ability to induce effective G4 aggregation, acting as non‐covalent cross‐linking agents. Abstract : A cytotoxic hug : Naphthalene diimide (NDI) dyads exhibit remarkable cytotoxicity (<10 nm ) on different cancer cell lines, which correlates to the length of the linker rather than the structure of the binding moieties (see figure).